From Tradition to Translation: A Systematic Review on the Pharmacological Actions of Eugenol Extracted from Ocimum Plants in Oxidative Stress, Inflammation, and Diabetes Mellitus - Permatananda, Pande Ayu Naya Kasih; I Wayan Putu Sutirta Yasa; I Wayan Sumardika; Made Ratna Saraswati; I Gde Suranaya Pandit (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Ocimum species, commonly known as basil, have a rich history in traditional medicine for various ailments. Eugenol, a primary bioactive compound found in several Ocimum species, has garnered significant scientific attention for its potential therapeutic properties. This systematic review aimed to comprehensively evaluate the pharmacological actions of eugenol extracted from Ocimum plants in the context of oxidative stress, inflammation, and diabetes mellitus. Methods: A systematic literature search was conducted across major scientific databases for studies published between 2013 and 2024 that investigated the effects of eugenol derived from Ocimum plants on oxidative stress, inflammation, and diabetes mellitus. The search strategy included keywords such as "eugenol," "Ocimum," "antioxidant," "anti-inflammatory," and "antidiabetic." Inclusion criteria for studies involving in vitro, in vivo, and clinical studies that specifically examined the pharmacological actions of eugenol extracted from Ocimum species in the aforementioned conditions. Data on study design, intervention, outcomes, and key findings were extracted and synthesized narratively. Results: The review identified ten key studies that met the inclusion criteria. These studies collectively suggested that eugenol extracted from Ocimum plants exhibited significant antioxidant activity by scavenging free radicals and enhancing endogenous antioxidant enzymes. Furthermore, eugenol demonstrated anti-inflammatory effects by modulating pro-inflammatory cytokines and inhibiting key inflammatory pathways such as NF-κB and COX. In the context of diabetes mellitus, studies indicated that eugenol could improve glucose metabolism by enhancing insulin sensitivity, protecting pancreatic beta cells, and inhibiting carbohydrate metabolizing enzymes. Conclusion: This systematic review provided a comprehensive overview of the pharmacological actions of eugenol extracted from Ocimum plants in mitigating oxidative stress, inflammation, and diabetes mellitus. The findings from the included studies supported the traditional uses of Ocimum species and highlighted the therapeutic potential of eugenol as a natural agent in managing these conditions. Further well-designed clinical trials are warranted to validate these preclinical findings and translate them into clinical applications.